171k views
0 votes
Solve for h -4(-6h - 7) = 9h + 10h - 7

2 Answers

4 votes

Answer:

h = -7

Explanation:

-4(-6h-7)= 9h+ 10h-7

24h+ 28=19h-7

-19. -28. -19 -28

5h -35

h= -7

User Monfresh
by
6.0k points
6 votes

Answer:

h=-7

Explanation:

-4(-6h - 7) = 9h + 10h - 7

24h+28=19h-7

Both side -28

24h+28-28=19h-7-29

24h=19h-35

Both side -19h

24h-19h=19h-19h-35

5h=-35

h=-7

User Sameera
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.